Impact of ownership structure on dividend payout policy: an Empirical study on listed plantation companies in Sri Lanka - Balagobei, S.; Thiruchchenthurnathan, T. (IISTE, 2016)
Ownership structure is one of the main dimensions of corporate governance. The aim of the study is to examine the impact of ownership structure on dividend payout policy of listed plantation companies in Sri Lanka. Fifteen listed plantation companies were selected as sample by using random sample method and secondary data was collected from the annual report of listed plantation companies in Sri Lanka during the period of 2010-2014. This study considers the ownership structure as independent variable which is measured by individual ownership structure, institutional ownership structure and foreign ownership structure and dividend payout policy as dependent variable which is measured by dividend payout ratio. For the purpose of analysis multiple regressions and Pearson’s correlation analysis were performed. The results reveal that foreign ownership structure has a significant impact on dividend payout policy. The study also found that foreign ownership structure is positive significantly correlated with dividend payout policy of listed plantation companies. Further individual ownership structure and institutional ownership structure are not significantly correlated with dividend payout policy. Higher the foreign ownership structure in listed plantation companies, the higher the dividend payout which is preferable for investors and it improves the dividends.
Keywords: Individual ownership structure; Institutional ownership structure; Foreign ownership structure; Dividend payout policy